Policy Intensions and the Folds of the Self. Issue 1 (3rd April 2013) - Webb, P. Taylor; Gulson, Kalervo N.
Abstract In this essay, P. Taylor Webb and Kalervo N. Gulson argue that educational policy is a spatial process and that implementation processes in particular produce crucial emergent geographies for policy research. Webb and Gulson describe how emergent geographies are produced when policy folds actors through senses and enactments of policy. The idea that policy is sensed and enacted is developed into the concept of a policy intension that extends approaches to spatial and, in particular, micropolitical analyses in policy research. Webb and Gulson conclude by discussing cartographical methods that better map the geographies of subjectivity produced through policy intensions.